2014
DOI: 10.1111/tpj.12445
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the phosphorylated BRI1 kinase domain and implications for brassinosteroid signal initiation

Abstract: Brassinosteroids, which control plant growth and development, are sensed by the membrane receptor kinase BRASSINOSTEROID INSENSITIVE 1 (BRI1). Brassinosteroid binding to the BRI1 leucine-rich repeat (LRR) domain induces heteromerisation with a SOMATIC EMBRYOGENESIS RECEPTOR KINASE (SERK)-family co-receptor. This process allows the cytoplasmic kinase domains of BRI1 and SERK to interact, trans-phosphorylate and activate each other. Here we report crystal structures of the BRI1 kinase domain in its activated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(210 citation statements)
references
References 70 publications
(203 reference statements)
8
199
1
2
Order By: Relevance
“…A GC core was also identified in the related LRR-RLKs Arabidopsis PepR1 (Qi et al, 2010) and BRI1 (Kwezi et al, 2007) and GC activity for both recombinantly expressed soluble proteins was demonstrated (Kwezi et al, 2007;Qi et al, 2010). On the other hand, a recently published analysis of the BRI1 crystal structure combined with activity assays of recombinantly expressed soluble BRI1 protein concluded that BRI1 does not possess GC activity (Bojar et al, 2014). While it seems likely that PSKR1 directly synthesizes cGMP that binds to and activates CNGC17, it is also conceivable that cGMP is generated by an as yet unidentified GC upon PSKR1 activation to drive CNGC17-dependent protoplast expansion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A GC core was also identified in the related LRR-RLKs Arabidopsis PepR1 (Qi et al, 2010) and BRI1 (Kwezi et al, 2007) and GC activity for both recombinantly expressed soluble proteins was demonstrated (Kwezi et al, 2007;Qi et al, 2010). On the other hand, a recently published analysis of the BRI1 crystal structure combined with activity assays of recombinantly expressed soluble BRI1 protein concluded that BRI1 does not possess GC activity (Bojar et al, 2014). While it seems likely that PSKR1 directly synthesizes cGMP that binds to and activates CNGC17, it is also conceivable that cGMP is generated by an as yet unidentified GC upon PSKR1 activation to drive CNGC17-dependent protoplast expansion.…”
Section: Discussionmentioning
confidence: 98%
“…cGMP had an inhibitory effect on PSKR1 kinase activity, suggestive of an autoregulatory signaling loop. A GC activity was also predicted for BRI1 (Kwezi et al, 2007;Wong and Gehring, 2013), but this was recently disputed based on crystal structure analysis of BRI1 and on enzyme assays (Bojar et al, 2014) such that the question of whether or not BRI1 produces cGMP remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that other alleles of HvBRI1, especially uzu1.256 with its milder phenotype and without the pronounced temperature sensitivity of uzu1.a, should be considered as more reliable alternatives for culm-length control in barley breeding. Interestingly, the uzu1.a mutation causes a change (His-857 to Arg) in a kinase surface domain (Bojar et al, 2014) that is not involved in ATP binding, nor does it interfere with the phosphorylation of the activation loop or with the position of the putative inhibitor BKI1 and SERK coreceptor binding site (Fig. 8,E and F).…”
Section: Lodging-resistant Barley In a Changing Climatementioning
confidence: 99%
“…The two views are rotated 90˚relative to each other. BRI1 in complex with ATP (red), the BRI1 activation loop with phosphorylation sites (in yellow), and the proposed protein-docking platform for the BRI1 inhibitor BKI or the SERK coreceptors (circled) are highlighted (Bojar et al, 2014). The numbering of amino acid residues refers to the barley peptide sequence shown in Supplemental Figure S8B online in which corresponding residue positions in Arabidopsis AtBRI1 or rice OSBRI1 are indicated.…”
Section: Genetic Characterization and Novel Alleles Of Hvbri1mentioning
confidence: 99%
“…The ligand-binding site is complete only once the co-receptor has been recruited by the receptor, with the hormone acting as a molecular glue that promotes the association of the receptor and co-receptor (101). In the complex structure, BRI1 and SERK1 are oriented in such a way that their C termini-which in the context of the full-length receptors connect to the transmembrane helices-are facing in the same direction and are in close proximity (7,101) (Figure 8a). A complex of BRI1 with SERK3/BAK1 revealed that different SERK proteins have very similar interactions with the receptor (119).…”
Section: Leucine-rich-repeat Receptor Kinase Activation By Shape-compmentioning
confidence: 99%